Homework trouble ; - Vail, Rachel (Vail, Rachel. Mama Rex & T., 2001)
Mama Rex has plans for a fun afternoon with T until she learns that he has a diorama about pigs due tomorrow, and so it's off to the library, the museum, and the park to gather information and supplies.